Tripping over our own feet : a critical discussion of Trade Related Intellectual Property Rights (TRIPS) with specific reference to their impact on South Africa's ability to combat HIV and AIDS - Brennan, Jade (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2008)
This thesis aims to look at the agreement on Trade Related Intellectual Property Rights (TRIPS) with specific reference to their impact on South Africa's ability to combat HIV and AIDS. It begins by looking at the history of patents and intellectual property rights and illustrates why and how the TRIPS Agreement came into existence. The TRIPS Agreement exemplifies the disparities between developed and developing countries and this can clearly be seen with regard to the provision of anti-HIV and AIDS drugs. The developing world deals with the bulk of the HIV and AIDS epidemic whilst the developed world holds most of the patents on the medication needed to treat those living with HIV and AIDS. This situation lends itself to a rift between patient rights on the one hand, and patent rights on the other. Traditionally the state has been the provider of rights such as health, but TRIPS alters this to include strong patent protection that is in line with neo liberal doctrine. The thesis examines these tensions with specific reference to South Africa's ability successfully to implement programmes to combat HIV and AIDS.
Keywords: Agreement on Trade-Related Aspects of Intellectual Property Rights, (1994); Trade regulation -- South Africa; Intellectual property -- South Africa; HIV (Viruses) -- South Africa; AIDS (Disease) -- South Africa; Patients -- Civil rights -- South Africa; Human rights -- South Africa